2^(2k+1)-2^-(2k-1)+2^-2k等于(A)A.2^-2k B.2^-(2k-1)C.2^-(2k+1)D.2设 k=0原式=2^(2*0+1)-2^-(2*0-1)+2^-(2*0)=2¹-2¹+2º=12^(-2k)=2^(-2*0)=2º=1
2^(2k+1)-2^-(2k-1)+2^-2k,等于()A.2^-2k B.2^-(2k-1)C.2^-(2k+1)D
1个回答
相关问题
-
(k+1)!(k+1)(k+2)为什么等于(k+1)[(k+2)!
-
n=1,略设n=k成立,k≥1即1+2+……+2k=k(2k+1)则n=k+11+2+……+2k+(2k+1)+(2k+
-
数列证明.由a2k-1,a2k,a2k+1成等差数列,及a2k,a2k+1,a2k+2成等比数列,得2a2k=a2k-1
-
求解2个线性方程 1.k1-k2+3k3=0 3k1+k2+k3=0 -k1+2k2-5k3=0 2.k1-k2+2k3
-
设k∈Z,2^-2k + 2^-2k-1 - 2^-2k+1 = ( )
-
若直线y=k1x+b1与直线y=k2x+b2的交点在x轴则.A k1=k2 B b1=b2 C k1b2=k2b2 D
-
已知数列{an},a1=1,a2k=a(2k-1)+(-1)^k,a(2k+1)=a2k+3k,k=1,2,3,...(
-
已知k>1,且a-b=2k,a^2+b^2+c^2=2k^2,a^2c^2+b^2c^2=k^4+2k^2,则以a,b,
-
记A(k)=x^(2k)-y^(2k),A(k+1)=x^(2k+2)-y^(2k+2)试用A(k)表示A(k+1) 帮
-
设A={x|x=2k,k∈Z},B={x|x=2k+1,k∈Z},C={x|x=2(k+1),k∈Z},D={x|x=2